2020
DOI: 10.1111/gcb.15311
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐induced acidification, not N‐nutrient, dominates suppressive N effects on arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal fungi (AMF) form symbiosis with most terrestrial plant roots, obtaining photosynthates in return for mineral nutrients. Ecological theories based on the economics of trading partnership predict that nutrient enrichment would suppress AMF. Experimental results from nitrogen (N) and phosphorus (P) additions, however, were highly variable, and the underlying mechanisms remain unclear. Here we show distinct AMF responses to soil N:P stoichiometry manipulations via gradients of long-term N an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 111 publications
(144 reference statements)
4
52
1
Order By: Relevance
“…The microbial biomass carbon and nitrogen were found to have a collaboratively opposite relationship with ammonium nitrogen and nitrate nitrogen (by negatively correlating with overall AMF community composition, structure, and nestedness). We confirmed a strong relationship between soil AMF and pH (Pan et al, 2020), but it may also be influenced by other surroundings and explained more by the partitioning of the Simpson and nestedness components.…”
Section: Discussionsupporting
confidence: 69%
“…The microbial biomass carbon and nitrogen were found to have a collaboratively opposite relationship with ammonium nitrogen and nitrate nitrogen (by negatively correlating with overall AMF community composition, structure, and nestedness). We confirmed a strong relationship between soil AMF and pH (Pan et al, 2020), but it may also be influenced by other surroundings and explained more by the partitioning of the Simpson and nestedness components.…”
Section: Discussionsupporting
confidence: 69%
“…Such elevational patterns of P‐addition and NP‐addition effects on priming can be explained by the elevational patterns of available P content and stoichiometric ratios of EOC and available N to available P (Figure S4). The available P content, EOC:available P, and available N:P have been widely used to indicate relative P availability for soil microbes (Fujita et al, 2017; Han, Feng, et al, 2020; Pan et al, 2020; Schleuss et al, 2020), and a higher P content and lower EOC:available P and available N:P ratios represent a higher soil P availability. The positive relationships of P‐addition effect on priming with available P, EOC:available P, and available N:P suggested that P availability for soil microbes is an important regulator controlling the intensity of P‐addition effect on priming.…”
Section: Discussionmentioning
confidence: 99%
“…C enzyme , carbon-acquisition enzyme (i.e. (Fujita et al, 2017;Han, Feng, et al, 2020;Pan et al, 2020;Schleuss et al, 2020), and a higher P content and lower EOC:available P and available N:P ratios represent a higher soil P availability. The positive relationships of P-addition effect on priming with available P, EOC:available P, and available N:P suggested that P availability for soil microbes is an important regulator controlling the intensity of P-addition effect on priming.…”
Section: Nutrient-addition Effects On Priming and Potential Regulatorsmentioning
confidence: 99%
“…The response of soil pH was positively correlated with the responses of AMF diversity and abundance to nutrient addition and was an important predictor for the response of AMF diversity and abundance. Previous researchers found that nutrient addition‐induced soil acidification can inhibit AMF colonization and mycelial development (Postma et al ., 2007; Sheldrake et al ., 2018; Pan et al ., 2020). Shifts in soil pH could directly impose a physiological constraint on AMF, which reduces the growth of some taxa when the soil pH falls outside a certain range and change in AMF communities (Kohout et al ., 2015; Xu et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%